Egyptian youth building a peaceful community – a case study - Sayed, Shereen Aly (AUC Knowledge Fountain, 2015)
This is a qualitative case-study that focuses on a sample of Egyptian youth-led initiatives that are working in the field of peace-building within “Selmiyah” movement. These initiatives have a variety of activities and interventions, working with different age groups from children to adults and in different communities, addressing different aspects of the peace education; such as conflict resolution skills, environmental issues, community organizing, and development-related projects. Using interviews, participant observations and document reviews; the researcher was able to provide a deeper view of the background and perceptions of the founders of these initiatives and the movement, the motives for creating the initiatives, the methodology and philosophy of the initiatives, the financial and organizational sustainability and the added value behind joining the movement. “Selmiyah” is a movement that was created by a group of youth who wanted to create a platform for collaboration and advocacy among all the CSOs actively working within the peacebuilding field; the movement includes now more than forty groups and a thousand individuals. This research also explains the reasons behind the creation of Selmiyah as a movement, the added value it can bring, the dynamics and processes of Selmiyah and the future of the movement. From the findings a number of things can be concluded, first peace is a comprehensive value and accordingly peace education work addresses different aspects of society, on awareness, skills and practice levels. Second, there is a need within Egyptian society for the concepts and tools that are being introduced by the initiatives working to promote peace culture. Third, the initiatives that are working on the ground have spent extensive time and effort on structuring their theoretical frameworks and curricula to provide good quality, if not high quality, services to their communities. Fourth, sustainability is a key challenge and thus it can be extremely beneficial to collaborate through a movement structure.